The relationship between training load, physical performance and physiological adaptations in Rugby football players: A systematic review - Paiva, Eduardo (2023)
Applying appropriate training loads in accordance with the defined objectives promotes optimal physical and physiological adaptations, reduces the likelihood of illness and injury and, therefore, increases the possibility of success during Rugby. The aim of this review was to compile and systematise the information in the literature on the association between training load variables (internal and external) and performance outcomes in Rugby. As such, the main objective will be to conduct a systematic review of the published literature to identify the physical and physiological performance variables in Rugby sport to monitor the training load. Following the preferred reporting item for systematic reviews and meta-analyses (PRISMA) and PICOS approach, the search was adapted and conducted systematically only in the PubMed database, which, in itself, also restricts the search spectrum of the paper, thus conferring a limitation to the present academic work. The search was conducted in PubMed throughout the possible temporal spectrum since there is still little robustness in the literature about rugby sports performance. Articles were selected by pre-defined selection criteria, including observational, randomised clinical and clinical trial studies. After further screening, and based on the inclusion criteria of the papers, the result of the analysis of the relevance of the studies, the final set of analysis resulted in 16 articles. From the studies compiled in this review, there seems to be a strong correlation between the perceived exertion (RPE) and the prescription and definition of the training load applied in Rugby athletes. The RPE reflects the most used and analysed variable throughout all the studies. Several articles reflect a strong relationship between the training load, the inter-individual capacity of each athlete and their tolerance to the load (player load).